Sources of Nitrogen Pollution in Upstream of Fenhe River Reservoir Based on the Nitrogen and Oxygen Stable Isotope - Ying Zhao; Jinhua Dang; Fei Wang (Journal of Chemistry)
Identification of nitrate sources is important for the management of rivers. In this study, stable isotopes (δ15N and δ18O) and a Bayesian model (stable isotope analysis in R, SIAR) were applied to identify nitrate sources and estimate the proportional contributions of multiple nitrate sources in the upstream of Fenhe River Reservoir that serves as a source of drinking water in Shanxi Province of North China. The results showed that the 86.4% of total nitrogen (TN) concentrations in the water samples exceeded the guided values of the Chinese Surface Water Environmental Quality Standard (GB 3838-2002). The influent of tributary and discharges of sewage caused the severe nitrogen pollution. SIAR was used to estimate the proportional contribution of three nitrate sources (sewage, inorganic fertilizer, and soil nitrogen). It was revealed that domestic sewage was the dominant nitrate source, and the contributions were 33%–41%. The contributions of inorganic fertilizer and soil to nitrogen load were 30%–31% and 31%–37%, respectively. Therefore, the pollution sources of nitrogen can be determined more accurately if the rules of sewage discharges are considered.